2017
DOI: 10.1111/apce.12180
|View full text |Cite
|
Sign up to set email alerts
|

Post‐privatization Ownership and Firm Performance: A Large Meta‐analysis of the Transition Literature

Abstract: This paper aims to perform a meta-analysis of the relationship between post-privatization ownership and firm performance using a large database of the transition literature. Baseline estimation of a meta-regression model that employs a total of 2894 estimates drawn from 121 previous studies indicated the superior impact of foreign ownership on firm performance in comparison with state and domestic private entities. However, it did not go as far as to comprehensively verify the series of hypotheses concerning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 57 publications
4
21
1
Order By: Relevance
“…Since then, a vast empirical literature has focused on the experience of the past three decades in the former USSR and Warsaw Pact countries. This literature, summarized and analysed recently by Iwasaki and Mizobata (), has found that indeed privatization has been associated with generally improved ‘performance’ in this context, with caveats related to details such as the level of product‐market competition and the specific institutional setting in which the privatization takes place.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a vast empirical literature has focused on the experience of the past three decades in the former USSR and Warsaw Pact countries. This literature, summarized and analysed recently by Iwasaki and Mizobata (), has found that indeed privatization has been associated with generally improved ‘performance’ in this context, with caveats related to details such as the level of product‐market competition and the specific institutional setting in which the privatization takes place.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of management and/or employee buy-outs (MEBO), insiders easily concentrated their shares. On the other hand, in the case of direct sales, large investors and foreign capitals had strong investment power and were given priority (Iwasaki and Mizobata, 2018). CEE and FSU countries adopted their own specific measures for privatization.…”
Section: Emergence Of Large Shareholders In Cee and Fsu Countriesmentioning
confidence: 99%
“…Hanousek et al (2015) examined corporate efficiency in old and new Europe and concluded that majority ownership does not ensure efficiency.4 The question of how differences in the types of owners and privatization methods employed can affect firm performance in transition economies has been examined byIwasaki and Mizobata (2018) by using a meta-analysis approach similar to the one described herein. 5 A meta-analysis conducted byHeugens et al (2009), on the other hand, included only studies focusing on companies in Asia.6 These emerging markets include 14 counties in South America, Asia, the Middle East, and Africa and the four CEE/FSU countries (i.e., the Czech Republic, Hungary, Poland, and Russia).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies in developed countries include research works by Megginson, Nash, and Van Randenborgh (1994), Sakr (2014), and Alipour (2013), while in developing and transition economies they include Boubakri, Cosset, and Guedhami (2008). Iwasaki and Mizobata (2018), Bachiller (2017) use a meta-analysis to explore the impact of privatization on firm performance. Pham (2017Pham ( , 2019, Sakr (2014), Alipour (2013), Loc, Lanjouw, and Lensink (2006), and Tran, Nonneman, and Jorissen (2015) compare changes in firm performance of privatized SOEs in Vietnam.…”
Section: Introductionmentioning
confidence: 99%